Korelasi Ketiadaan Peran Ayah dengan Regulasi Emosi pada Remaja Perempuan - Neva Sefanya; Meike Kurniawati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to explore the relationship between the absence of a father's role and emotional management in adolescent girls. The background of this study is based on the need to recognize the psychological consequences of the lack of a father's role in the lives of adolescent girls in order to support their emotional well-being. In this study, a quantitative approach was used with a correlational analysis method. Data collection was carried out by distributing questionnaires to adolescent girls and then analyzing them using the Spearman method. The findings of this study indicate a significant negative relationship between the absence of a father's role and emotional management. The absence of a father's role has a significant impact on how adolescent girls manage their emotions. This study provides an important message for parents, especially fathers, to be more actively involved in their children's lives, both physically and emotionally, in order to help develop good emotional management skills in children.